Energy Expenditure and Fitness Response Following Once Weekly Hill Climbing at Low Altitude - Tian, Y.; He, Z.; Xu, C.; Huang, C.; Lee, J.-H.; Li, R.; Zhou, J.; Zhao, J.; Wang, M.; Hong, P.; Mc Naughton, L. R. (International Journal of Sports Medicine, 2015)
This work sought to determine the fitness responses and energy expenditure (EE) following once-weekly hill climbing for 16 weeks on different slopes. A cohort of 98 healthy, sedentary subjects (49 female, 49 male) completed the program at their preferred climbing pace. Body composition, resting metabolic rate (RMR) and VO2max were measured. EE was measured on 4 slopes (11.6°, 19.9°, 14.9°, and 28.6°) at the subjects’ preferred speed. In males, weight, body mass index, fat mass significantly decreased (P<0.05), and RMR showed an increasing trend, but the difference was not significant (P=0.051). In females, the muscle mass increased significantly, and fat (%) and fat mass significantly decreased (P<0.05). Absolute and relative of VO2max, ventilation (VE) improved significantly in both sexes (P<0.01). Energy expenditure was similar on different slopes, but shows gender-specific values of approximately 50.4 and 33.6 kJ/min for males and females, respectively. The regression equation of EE (kJ/min)=[1.724×(female=1, and male=2)+(−0.072×age)+0.106×weight+0.024×HR+0.136×slope+1.487×velocity]×4.2. In conclusion, hill climbing at a subjects’ preferred velocity is a vigorous-intensity physical activity for energy cost and, performed once weekly, enhances cardiorespiratory fitness and reduces fat mass, therefore making it a viable exercise for most people.
Keywords: VO2max; resting metabolic rate; body composition; physical activity